2017
DOI: 10.1002/ehf2.12137
|View full text |Cite
|
Sign up to set email alerts
|

Association between matrix metalloproteinase‐9 and worsening heart failure events in patients with chronic heart failure

Abstract: AimsMatrix metalloproteinase (MMP) is up‐regulated during heart failure (HF) and influences ventricular remodeling. We hypothesized that disparity between MMP‐9 and tissue inhibitors of MMP‐1 (TIMP‐1) results in clinical manifestations and is related to prognostic risk in patients with chronic HF.Methods and resultsPlasma levels of MMP‐9, TIMP‐1, and brain natriuretic peptide (BNP) were measured in 173 patients with chronic HF. Combined endpoints of worsening HF events were assessed during follow‐up (median 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 43 publications
0
48
0
5
Order By: Relevance
“…Elevated MMP-2, longer AF duration, and atrial extracellular matrix remodeling of AF further increased the risk of difficulties in restoring sinus rhythm in AF patients [29-31]. Active myocardial remodeling is accompanied by enhanced activation of MMP-2 and MMP-9 [32, 33]. In the present study, the use of medications was balanced before any comparisons were made.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated MMP-2, longer AF duration, and atrial extracellular matrix remodeling of AF further increased the risk of difficulties in restoring sinus rhythm in AF patients [29-31]. Active myocardial remodeling is accompanied by enhanced activation of MMP-2 and MMP-9 [32, 33]. In the present study, the use of medications was balanced before any comparisons were made.…”
Section: Discussionmentioning
confidence: 99%
“…Как показано в ряде иссле- дований, TIMP-1 способен связываться с неактивной формой рro-MMP-9, образуя комплекс, в котором ТИМП-1 сохраняет свою способность ингибировать активность других активных MMП. Известно, что высокие значения ММП-9 и нарушение баланса ММП-9/ТИМП-1 являются независимым предикто-ром неблагоприятных событий у пациентов с ХСН [13]. Данный факт подтверждается и нашим исследо-ванием: у пациентов с СНсрФВ и неблагоприятным исходом после КХО отмечалась высокая экспрессия ММП-9 и умеренная ТИМП-1, что отражает их дис-баланс.…”
Section: таблица 2 сравнительная характеристика данных эхокг у пациенunclassified
“…In particular, MMP‐2 and MMP‐9 levels are elevated in patients with LV volume overload, which contributes to myocardial collagen accumulation and subsequent cardiac dysfunction. Further, both MMPs have predictive value regarding cardiovascular events, including mortality . Myocardial remodeling processes are also closely associated with inflammation processes, and published data have shown that extensive inflammation magnifies these cardiac structural alterations and thus may accelerate the progression of heart failure (HF) .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Increased cardiac collagen synthesis and impaired degradation in response to pressure and volume overload in patients with MR lead to an imbalance of collagen metabolism and contribute to collagen accumulation and consequently cardiac structural remodeling processes, myocardial stiffness, and fibrosis. [14][15][16] Matrix metalloproteinases (MMPs) are important regulators of ECM turnover and myocardial remodeling processes. [14][15][16] In particular, MMP-2 and MMP-9 levels are elevated in patients with LV volume overload, which contributes to myocardial collagen accumulation and subsequent cardiac dysfunction.…”
mentioning
confidence: 99%